Productive and reproductive performance of first lactation purebred Holstein versus Swedish red & white×Holstein in central Argentina - Piccardi, Mónica Belén (2014)
The aim of this work was to compare productive and reproductive performance between pure Holstein (H) and Swedish Red & White×Holstein crossbred (SRB/H) in first lactation dairy cows from the central region of Argentina. This study included 450 lactations from a commercial dairy of central-southern Argentina. The differences in mean daily milk yield, days to first breeding (DFB) and number of services per pregnancy (NS/P) between genotypes were evaluated. A Cox proportional hazard regression model was fitted to evaluate the breed effects on days open (DO) and adjusting by calving season and calving year. Days open were estimated trough survival curves for H breed and SRB/H crossbred using Kaplan–Meier method. Finally, average lactation curves were modeled for each genotype using a non-linear mixed model. Daily milk yield was not significantly different between genotypes. However, the cumulative 305-d yield and peak milk yield for pure H was higher than for SRB/H. Days to first breeding was lower for SRB/H than pure H. The NS/P was higher for pure H than for SRB/H. Regarding DO, SRB/H breed had 1.00–1.71 higher likelihood to become pregnant than pure H. Days open of 50% of pure H was 30 d higher than for SRB/H. The results showed that SRB/H crossbred were superior to pure H in terms of reproductive performance but inferior in terms of productive performance. Further studies may help to determine if the economics of dairying justifies the use of crossbreeding as a herd fertility enhancing tool.